Kai-Xin-San, a standardized traditional Chinese medicine formula, up-regulates the expressions of synaptic proteins on hippocampus of chronic mild stress induced depressive rats and primary cultured rat hippocampal neuron. (4th December 2016) - Zhu, Yue; Duan, Xiuzhu; Cheng, Xiaoxuan; Cheng, Xiaonan; Li, Xu; Zhang, Liu; Liu, Pei; Su, Shulan; Duan, Jin-ao; Dong, Tina Ting-Xia; Tsim, Karl Wah-Keung; Huang, Fei
Abstract: Background: Kai-xin-san (KXS), composed of Ginseng Radix et Rhizoma, Polygalae Radix, Acori Tatarinowii Rhizoma and Poria, is a famous Chinese medicinal formula applied for treating stress-related psychiatric disease with the symptoms such as depression, forgetfulness and dizziness. Dependent on the symptom differentiation of patients, the composition ratio of KXS was varied and one ratio of 3:2:2:3 was widely applied. However, its molecular mechanism has seldom been investigated. Purpose: We aimed to reveal the action mechanism of KXS on anti-depression on synaptic protein regulation in both in vivo and in vitro models. Study design/methods: Firstly, the anti-depression effect of KXS was evaluated on a chronic mild stress induced depressive animal model and the mRNA expressions of various synaptic proteins in hippocampus of the depressive rat brains were determined. Then, KXS with different ratios as well as single herb were further evaluated on rat primary cultured hippocampus neurons and the possible signaling pathway was explored. Results: Intra-gastric administration of a chemically standardized KXS for only 6 h significantly alleviated the CUMS-induced depressive symptoms displayed by enhanced sucrose consumption and this effect was maintained after daily treatment for seven days. Simultaneously, the mRNA expressions of various synaptic proteins in hippocampus were regulated. Among these synaptic proteins, synaptotagmin (pre-synaptic marker) and post synaptic density protein (post-synaptic marker), with the higher altered magnitude on animal model, were further evaluated on rat primary cultured hippocampus neurons. After neuronal cultures treated with three ratios of KXS at the early and late stages of its life episode, the expression levels of synaptotagmin and PSD95 were both enhanced dramatically via stimulating cAMP dependent pathway. However, different ratio exerted different efficacy. The ratio with higher amounts of Ginseng Radix et Rhizoma and Polygalae Radix showed better effect in early life episode while higher amounts of Acori Tatarinowii Rhizoma and Poria behaved better in late life episode. The contribution of single herb on expressions of synaptic proteins was also evaluated. Conclusions: KXS was beneficial for synaptogenesis by inducing synaptic protein expressions, which might account for its anti-depression effect. Graphical abstract: